Determination Sun Protecting Factor (SPF) Of Krokot Herbs Extract (Portulacaoleracea L.) - Widya Astuty Lolo; Sri Sudewi; Hosea Jaya Edy (Universitas Sebelas Maret, 2017)
Purslane is a plant that thrives in open areas and has a fairly high water content. Hereditary purslane plant has been used for skin protection from the sun. The aim of this study is to determine the value of Sun Protecting Factor (SPF) of ethanol extracts, soluble and insoluble fractions of ethyl acetate from purslane herb.Extraction using maceration method by ethanol 90%. Fractionation process is the partition obtained soluble and insoluble fractions of ethyl acetate. Absorbance values read using UV-VIS spectrophotometry at a wavelength of 290-320 nm. SPF value is obtained for the ethanol extract 19.495, 20.829 for the soluble fraction of ethyl acetate and 30.055 for an insoluble fraction of ethyl acetate.